Improved immobilization of Re(VII) from aqueous solutions via bimetallic Ni/Fe0 nanoparticles: Implications towards Tc(VII) removal - Maamoun, Ibrahim; Tokunaga, Kohei; Dohi, Terumi; Kanno, Futoshi; Falyouna, Omar; Eljamal, Osama; Tanaka, Kazuya (Frontiers in Nuclear Engineering, 2023)
In this work, bimetallic nickel/iron nanoparticles (Ni/Fe0) were prepared to enhance rhenium (Re(VII)) immobilization from aqueous solutions, as the surrogate of technetium (Tc(VII)). Two synthesis approaches of Ni/Fe0, pre-, and post-nucleation, were investigated towards Re(VII) removal. Different characterization techniques were considered to elucidate the physicochemical features of the fresh and reacted materials, such as scanning transmission electron microscopy-energy dispersive X-ray spectroscopy (STEM-EDX), X-ray diffraction (XRD), and X-ray absorption near edge spectroscopy (XANES). The influence of several reaction parameters on Re(VII) removal was investigated, including Ni/Fe0 ratio, dosage, initial pH, temperature, and initial concentration. Results showed a promising potential of Ni/Fe0, either pre- or post-nucleation synthesized, in Re(VII) removal, especially at the early stage of the reaction, where Ni/Fe0: 0.4 yielded almost full removal efficiency of initial 15.0 µM-Re(VII) within the first 10 min of reaction. Even at low Ni/Fe0 dosages, such as 0.25 and 0.5 g/L, reasonable removal efficiency was achieved after 2 hours reaction time of ~73% and ~98%, respectively. Unlike acidic/neutral pH, alkaline conditions were not favorable for Re(VII) removal by Ni/Fe0 owing to the delayed aqueous corrosion of Fe0-core resulting in insufficiency of electrons available for Re(VII) reduction. The reductive abilities were confirmed by XANES, revealing Re(VII) reduction to Re(IV)/(III) by the released electrons from Fe0-core in both Fe0 and Ni/Fe0 materials. Pseudo-first- and second-order kinetic models were suitable to describe Re(VII) removal by Ni/Fe0, implying physical and/or chemical processes were involved. Zeta potential measurements depicted the point of zero charge (pHPZC) of Fe0 and Ni/Fe0 to be 8.24 and 7.63, respectively, suggesting the involvement of electrostatic sorption of ReO4- on the positively charged surface of Ni/Fe0. The occurrence of multi- and mono-layer sorption within Re(VII) removal process was implicated, following Freundlich and Sips isotherm models. The presence of Ni0/NiO on Fe0-surface resulted in providing an efficient electron-transfer medium that facilitated Re(VII) reduction, leading to impressive kinetic rates. Overall, our study provided valuable insights into the use of Ni/Fe0 for Re(VII) removal from water and offered guidance for future research in such an aspect towards the pilot-scale applications of Tc(VII) removal from nuclear wastewater.